LANGUAGE DEVELOPMENT IN A 1-YEAR-7-MONTH-OLD CHILD BASED ON PHONOLOGICAL AND SEMANTIC ASPECTS - Ningsih, Ningsih (Lantern: Journal of Language and Literature, 2024)
he objective of this study is to analyze the language development of a 1-year-7-month-old child named Ary, with a focus on phonological and semantic aspects. The research was conducted through a three-month observation period, during which interactions between Ary and his surroundings, particularly his mother, were meticulously documented.The findings indicate that, in the phonological aspect, Ary has demonstrated the ability to produce various words, although there are pronunciation errors such as with the letters "L" and "R" (puyang for ennen, kokok for rokok). These errors are typical and reflect the articulation development process at his age. In the semantic aspect, the child has begun to demonstrate an understanding and use of words with more complex meanings, such as api for "hot" and amen for "prayer."The study also found that communication strategies such as motherese, recasting, echoing, and expanding play a crucial role in supporting the child's language development. These strategies provide linguistic stimulation that helps the child enrich his vocabulary, improve his pronunciation, and build simple sentence structures. The study's findings underscore the pivotal role of social interaction, particularly that of parents, in facilitating children's language development.These findings resonate with the theories propounded by Vygotsky and Brunner, which accentuate the significance of environmental support and the sociocultural context in attaining optimal language development.